Understanding political skills and leadership styles on public satisfaction in women politicians - Elly Malihah; Siti Nurbayani; Siti Komariah; Etty Sisdiana; Yendri Wirda; Lingga Utami; Rengga Akbar Munggaran (Cogent Social Sciences)
Women’s presence in the Indonesian parliament is an opportunity to be involved in the democratic processes. Their political skills and leadership styles can be studied through the gender equality, disability and social inclusion (GEDSI) approach. This research aims to investigate the effect of political skills and leadership styles of women politicians who implement the GEDSI on public satisfaction. This study based on a quantitative, the quantitative stage held a survey of 188 respondents which were then analyzed using PLS-SEM. To strength information, we derived from interviews and focus group discussions with stakeholders and women politicians. The research shows that social astuteness, especially political skills, directly and indirectly, influenced public satisfaction with the partial mediating role of achievement leadership. Political skills through apparent sincerity had interactions with public satisfaction, where the directive leadership could be a partial mediation role. Finally, cognitive social capital as political skills influenced public satisfaction with the partial mediating roles of supportive leadership, participative leadership and achievement leadership. This study also found that network ability and interpersonal influence had no significant effect on public satisfaction. Women politicians who apply the GEDSI approach become their political skills that benefit a leadership style as well as encourage more accommodative and substantial political decision-making.